That's my country belonging to me : Aboriginal land tenure and dispossession in nineteenth century Western Victoria - Clark, Ian D., 1958- (Melbourne : Heritage Matters, 1998)
A historical geography of dispossession in which social organisation boundaries and nomenclature of clans of Dhauwurd wurrung, Djab wurrung, Djadja wurrung, Djargurd wurrung, Gadabanud, Girai wurrung, Gulidjan, Jardwadjali, Watha wurrung and Wergaia were reconstructed from historical sources, mostly Robinson papers and some linguistic comparison; documented effects of dispossession on clan estates from European occupation of land giving examples of resulting negative and positive race relations and removal of clans to Lake Condah and Framlingham; discussed inter-clan conflict and enmity of local clans to foreign Aboriginal people; gave examples of squatters who massacred, intimidated and excluded clans from their lands and resources and also sqatters who welcomed and employed clans; provided much biographical and place name information relating to clans; appended a register of clans of Western Victoria.
Includes bibliographical references (p. 185-200).
Keywords: Aboriginal Australians -- Victoria -- Land tenure -- History; Land tenure -- Victoria -- History; Mardidjali people (S16) (Vic SJ54-03); Social organisation - Clans; Wathawurrung / Wada wurrung / Wathaurong people (S29) (Vic SJ54-12); Race relations - Violent; Djabwurrung / Dyabwurung people (S26) (Vic SJ54-08); Colonisation; Giraiwurung / Girrea / Kirrae Whurrong people (S25) (Vic SJ54-12); Jardwadjali people (S27) (Vic SJ54-03); Wergaia / Wotjobaluk people (S17) (Vic SI54-15); Culture - Relationship to land; Djadja wurrung / Dyadyawurung / Dja Dja Wrung people (S31.1) (Vic SJ54-04); Western Victoria (W Vic)